2014
DOI: 10.1037/a0038055
|View full text |Cite
|
Sign up to set email alerts
|

Divergent productions of metaphors: Combining many-facet Rasch measurement and cognitive psychology in the assessment of creativity.

Abstract: This article presents a new method for the assessment of creativity in tasks such as "The camel is ________ of the desert." More specifically, the study uses Tourangeau and Sternberg's (1981) domain interaction model to produce an objective system for scoring metaphors produced by raters and the many-facet Rasch measurement to model the rating scale structure of the scoring points, item difficulty, and rater severity analysis, thus making it possible to have equated latent scores for subjects, regardless of ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 46 publications
1
24
0
Order By: Relevance
“…For example, Beaty and Silvia shows that crystallized knowledge could only predict individuals' ability to generate conventional metaphors (r = .30), but fluid intelligence predicts creative metaphor production (r = .45) and is not associated with conventional metaphors production. We replicated this finding observing a strong association of divergent production of metaphors with fluid reasoning (r =.60, similar to what was found in Primi, 2014). David, Morais, Primi and Miguel (2014) found that scores on Metaphor Creation Test has a strong association with grades in high school Portuguese students.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…For example, Beaty and Silvia shows that crystallized knowledge could only predict individuals' ability to generate conventional metaphors (r = .30), but fluid intelligence predicts creative metaphor production (r = .45) and is not associated with conventional metaphors production. We replicated this finding observing a strong association of divergent production of metaphors with fluid reasoning (r =.60, similar to what was found in Primi, 2014). David, Morais, Primi and Miguel (2014) found that scores on Metaphor Creation Test has a strong association with grades in high school Portuguese students.…”
Section: Discussionsupporting
confidence: 86%
“…Metaphors task is defined as "an instrument for evaluation of cognitive components of creativity" (Primi, Miguel, Couto, & Muniz, 2007, p.198). Recent studies shows a stronger role of intelligence in creative thinking than previously thought especially implicating executive functions, working memory and fluid intelligence in the production of creative metaphors (Benedeck et al, 2013;Chiappe & Chiappe, 2007;Kazmerski, Blasko, & Dessalegn, 2003;Primi, 2014;Silvia & Beaty, 2012). For example, Beaty and Silvia shows that crystallized knowledge could only predict individuals' ability to generate conventional metaphors (r = .30), but fluid intelligence predicts creative metaphor production (r = .45) and is not associated with conventional metaphors production.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Creative people might do these activities more creatively, but not necessarily more repeatedly (Baer, 2016). To complicate matters further, recent studies (Primi, 2014;Silvia, 2015) have stated that divergent thinking and intelligence are more closely related than initially thought.If this is generally the case, then the variance of creative achievement may largely be attributed to differences in intelligence, not to differences in divergent thinking ability (Hocevar & Bachelor, 1989;Plucker, 1999a;Plucker & Renzulli, 1999). For instance, most statistical analyses employed in Torrance's (1972a) study were simple correlation coefficients that do not control for the effect of other external variables.…”
mentioning
confidence: 99%
“…Perhaps this is not surprising given that many of the creativity instruments were developed and standardized before the advent of modern psychometric analyses (Fishkin in creativity research, and although limited, their results are promising. These efforts addressed some critical issues in creativity measurement, such as evaluating reliability and validity (Chermahini, Hickendorff, & Hommel, 2012;Karwowski, 2014;Lee, Lee, & Youn, 2005;Primi, 2014;Silvia, 2011;Silvia et al, 2008;Wang, Ho, Cheng, & Cheng, 2014;Zampetakis, 2010), testing domain-specificity of creativity (Barbot, Tan, Randi, SantaDonato, & Grigorenko, 2012;Chen et al, 2006;Silvia, Kaufman, & Pretz, 2009), evaluating the rater's effect on performance assessment (Hung, Chen, & Chen, 2012) and modelling relationships between creativity and other constructs (Nusbaum & Silvia, 2011;Silvia, 2008). Expanding the use of these modern analyses could provide a better understanding of conflicting results in creativity research.…”
Section: Psychometric Propertiesmentioning
confidence: 99%